Analisis Kesalahan Umum dalam Tata Persuratan dan Upaya Pencegahannya: Studi Kasus di Yayasan Pendidikan Prima Swarga Bara (YPPSB) - Iswanto; Fitriah Amina; Siti Maryam (STIT Syekh Muhammad Nafis Tabalong, 2023)
The Prima Swarga Bara Education Foundation (YPPSB) recognizes the importance of proper and effective writing in ensuring good communication with various parties, including students, parents, staff, and partners. This research uses a qualitative approach with text analysis and interview methods to delve into the complexities of writing errors. This approach is chosen because the main focus of the research lies in identifying and understanding in depth the errors in official letters through careful analysis of letter examples. Analysis of common grammatical errors found, such as the use of incorrect words, ineffective sentences, and misuse of punctuation. In the case of the announcement letter for the results of the YPPSB PPDB 2021-2022, there is an error in the section